The Timber trade: an introduction to commercial aspects - Leigh, Jack H. (New York Pergamon Press, 1971)
Serves as a guide to the commercial aspects of Timber Trade.
Includes index
kjo 15/01/2019
Loans
Keywords: FOREST PRODUCTS MARKET; FOREST PRODUCTS TRADE